PKM. BISNIS KULINER DI ERA NEW NORMAL PADA KEGIATAN BAKTI SOSIAL UPMI 2020 - Putu Dessy Fridayanthi; I Komang Sukendra; Gusti Ayu Made Puspawati; A A Istri Mirah Dharmadewi (LPPM Universitas PGRI Mahadewa Indonesia, 2021)
In the context of implementing the Tri Dharma of Higher Education, especially the 3rd dharma, namely community service, Universitas PGRI Mahadewa Indonesia held a 2020 Social Service in Batubulan Village, Sukawati District, Gianyar Regency on Thursday - Friday, 17 - 18 December 2020. Social service is one of the activities designed as a form of student contribution to society directly. In a business, the ability of business actors to change their perspective on obstacles is very important. When most people see problems as obstacles, an entrepreneur must be able to look for opportunities from existing problems. The objectives of social service activities are: (1) To increase awareness among students and lecturers, (2) To provide assistance to people in need, (3) To generate a social spirit as a team in community service. The method used was socialization and cooking demonstrations by inviting several representatives of Ms. PKK from every banjar in Batubulan village. Businesses that ignore digital technology are actually experiencing a slump. In these transitional or new normal times, the aspect of business digitization also has the potential to have a very large positive impact. Service can be an innovation also in the midst of a new normal situation. The instantaneous gains gained by lowering the quality of food can have long-term effects. By maintaining good quality, the business will continue to run.